CFD based design optimization of dimples induced on Blended Wing Body airframe using the Taguchi method - Haris Ali; Mohammad Rasidi Rasani; Zambri Harun; Muhammad Ashhad Shahid (PLoS ONE, 2025)
This research focuses on optimizing the design of dimples on a Blended-Wing-Body (BWB) airframe to enhance aerodynamic efficiency. Dimples serve as a passive flow control method intended to improve aerodynamic properties. Employing the Design of Experiments (DOE) framework and utilizing the Taguchi method, we examined five dimple design variables across three distinct levels. These variables included dimple placement, indentation depth, diameter, spacing between dimples, and the number of dimple rows on the BWB wing. An L18 orthogonal array (OA) was implemented to assess the impact of these variables on the drag coefficient (CD), lift coefficient (CL), and lift-to-drag ratio (L/D), which were used as performance metrics. High-fidelity Computational Fluid Dynamics (CFD) simulations were conducted for each of the eighteen configurations outlined by the L18 OA, across angles of attack ranging from 0° to 8°. Signal-to-Noise Ratio (SNR) analysis and Pareto Analysis of Variance (ANOVA) revealed that the dimple diameter had the most significant impact on both CD and L/D, contributing 35.19% and 40%, respectively, while the indentation depth showed the least influence. The study identified an optimal combination of design variables (A1B1C1D3E3), which minimizes CD and maximizes L/D. This work provides actionable guidelines for dimple design as a passive flow control method in aerospace applications.